Field testing and evaluation of a two layer soil water balance model - MOHANAN C. K; Dr. Hajilal M. S (Guide) (Tavanur 1997 Kelappaji College of Agricultural Engineering and Technology)
Field testing and evaluation of a two layer soil water balance model
Field testing and evaluation of a two layer soil water balance model